Influence of spore morphology on spectrophotometric quantification of Trichoderma inocula - Georg Schütz; Dietmar Haltrich; Lea Atanasova (BioTechniques, 2020)
Species of the genus Trichoderma are filamentous fungi commonly used in research, industry and agriculture. Trichoderma reesei strains are prominent producers of cellulolytic and hemicellulolytic enzymes as well as being expression hosts; several other species such as T. atroviride might be exploited as biocontrol agents. A careful preparation of Trichoderma inocula, which consists mainly of conidia (asexual spores), is of immense importance. Conidia concentration is still mostly determined with the help of a hemocytometer; however, as a more accurate and time-saving alternative, absorbance can be used to estimate fungal spore counts. We established a spectrophotometric method for fast and reliable preparation of Trichoderma inocula by evaluating the effect of size, shape and pigmentation of the conidia at different wavelengths.